An Exploration of New Energy Storage System: High Energy Density, High Safety, and Fast Charging Lithium Ion Battery. (14th November 2018) - Wu, Yingqiang; Wang, Wenxi; Ming, Jun; Li, Mengliu; Xie, Leqiong; He, Xiangming; Wang, Jing; Liang, Shuquan; Wu, Yuping
Abstract: Rechargeable lithium ion battery (LIB) has dominated the energy market from portable electronics to electric vehicles, but the fast‐charging remains challenging. The safety concerns of lithium deposition on graphite anode or the decreased energy density using Li4 Ti5 O12 (LTO) anode are incapable to satisfy applications. Herein, the sulfurized polyacrylonitrile (SPAN) is explored for the first time as a high capacity and safer anode in LIBs, in which the high voltage cathode of LiNi1/3 Co1/3 Mn1/3 O2 (NCM‐H) is further introduced to configure a new SPAN|NCM‐H battery with great fast‐charging features. The LIB demonstrates a good stability with a high capacity retention of 89.7% after 100 cycles at a high voltage of 3.5 V (i.e., 4.6 V vs Li + /Li). Particularly, the excellent rate capability is confirmed and 78.7% of initial capacity can still be delivered at 4.0C. In addition, 97.6% of the battery capacity can be charged within 2.0C, which is much higher than 80% in current fast‐charging application standards. The feature of lithiation potential (>1.0 V vs Li + /Li) of SPAN avoids the lithium deposition and improves the safety, while the high capacity over 640 mAh g −1 promises 43.5% higher energy density than that of LTO‐based battery, enabling its great competitiveness to conventional LIBs. Abstract : Sulfurized polyacrylonitrile (SPAN) is explored for the first time as a high capacity and safer anode in a lithium ion battery, in which the high voltage cathode of LiNi1/3 Co1/3 Mn1/3 O2 (NCM‐H) is further introduced to configure a new SPAN|NCM‐H battery with great fast‐charging features. Excellent rate capability is confirmed and 97.6% of the battery capacity can be charged within 2.0C.